Diversity in angiosperm flora of Teknaf wildlife sanctuary, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2013)
Teknaf Wildlife Sanctuary has been explored to assess angioperm diversity using traditional taxonomic techniques during 2010 to 2011. The assessment has resulted inrecording of total 535 angioperm species under 103 familiies and 370 genera. For each species scientific name, Bangla name (whenever available), family and habit are provided. Of 535 species, 178 represented by herbs, 110 by shrubs, 150 by trees, 87 by climbers and 10 by epiphytes. In Magnoliopsida (dicots), Fabaceae is the largest family represented by 38 species, while in Liliopsida (monocots), Poaceae is the largest family represented by 29 species.DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17389Bangladesh J. Plant Taxon. 20(2): 145-162, 2013